Internalizing sexism within close relationships Perceptions of intimate partner's benevolent sexism promote women's endorsement of benevolent sexism. [article]. - Hammond, Matthew D.
The current demonstrated that women's adoption of benevolent sexism is influenced by their perceptions of their intimate partners' agreement with benevolent sexism. In 2 dyadic longitudinal studies, committed heterosexual couples reported on their own sexism and perceptions of their partner's sexism twice across 9 months (Study 1) and 5 times across 1 year (Study 2). Women who perceived that their male partner more strongly endorsed benevolent sexism held greater and more stable benevolent sexism across time, whereas lower perceptions of partners' benevolent sexism predicted declines in women's benevolent sexism across time. Changes in men's endorsement of sexism were unrelated to perceptions of their partner's sexist attitudes. The naturalistic change in sexist attitudes shown in Studies 1 and 2 was supported by experimental evidence in Studies 3 and 4: Manipulations designed to increase perceptions of partner's benevolent sexism led women (but not men) to report greater benevolent sexism. Studies 3 and 4 also provided evidence that perceptions of partner's benevolent sexism fosters perceived regard and relationship security in women, but not men, and these relationship factors enhance attitude alignment. Discriminant analyses demonstrated that these effects were specific to women's perceptions of partner's, rather than societal, levels of sexism. In sum, these studies illustrate that women endorse benevolent sexism when they perceive that the reverence and security that benevolent sexism promises women and accessible in their relationships. -- (from the authors)